Peningkatan Daya Saing Jamu Tradisional Medan Krio: Sinergi Teknologi Tepat Guna dan Manajemen Usaha - Maryati Evivani Doloksaribu; Adriana YD Lumbangaol; Ainul Mardhiyah; Mukti Hamjah Harahap; Dedy Husrizal Syah (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2026)
The traditional herbal medicine (jamu) business group in Medan Krio Village faces systemic challenges of low productivity due to manual processing and a lack of basic financial bookkeeping knowledge. This community service program aims to accelerate micro-enterprise productivity and efficiency through integrated operational and bookkeeping strategies. Implementation methods included situation analysis, focus group discussions, practical training and handover of appropriate technology (TTG) tools, alongside bookkeeping and business management training. Implemented solutions consisted of two wet jamu grinding units (20–30 kg/hour capacity), an 80-cm diameter cauldron, a 50-liter storage container, and a financial ledger. Results showed a 60–70% leap in operational efficiency (reducing time from 6–8 hours to 2–3 hours) and a 100% increase in daily output capacity (reaching 10–20 liters per batch). Partners' managerial literacy surged by 85–90% in preparing independent income statements separate from household finances. The synergy of production mechanization and managerial literacy successfully revolutionized the traditional jamu business ecosystem into an efficient, sustainable micro-enterprise.